Duflo-Moore Operator for The Square-Integrable Representation of 2-Dimensional Affine Lie Group - Edi Kurniadi; Nurul Gusriani; Betty Subartini (Jurnal Matematika MANTIK, 2020)
In this paper, we study the quasi-regular and the irreducible unitary representation of affine Lie group of dimension two. First, we prove a sharpening of Fuhr’s work of Fourier transform of quasi-regular representation of . The second, in such the representation of affine Lie group is square-integrable then we compute its Duflo-Moore operator instead of using Fourier transform as in F hr’s work.